Plasma membrane transbilayer asymmetry of PI(4,5)P2 drives unconventional secretion of Fibroblast Growth Factor 2 - Kaur, Manpreet; Lolicato, Fabio; Nickel, Walter (Nature Communications, 2025)
Unconventional secretion of Fibroblast Growth Factor 2 (FGF2) is mediated by direct translocation across the plasma membrane. This process is initiated by PI(4,5)P2-dependent FGF2 oligomerization at the inner plasma membrane leaflet. PI(4,5)P2 is a non-bilayer lipid that accumulates at sites of FGF2 oligomerization, imposing severe membrane stress that is relieved by the formation of a lipidic membrane pore. At the outer leaflet, FGF2 oligomers are captured and disassembled by the heparan sulfate proteoglycan Glypican-1 (GPC1), making available FGF2 to engage in ternary signaling complexes on cell surfaces. Using an in vitro reconstitutions system, this study provides direct evidence that transbilayer asymmetry of PI(4,5)P2 promotes rapid kinetics of membrane pore formation. Likewise, FGF2 secretion from cells is inhibited when PI(4,5)P2 plasma membrane transbilayer asymmetry is disrupted. We propose the asymmetric distribution of PI(4,5)P2 to lower the energetic barrier for membrane pore formation, enabling rapid kinetics of FGF2 membrane translocation into the extracellular space.
Gesehen am 24.02.2026